Students' Ability in Writing Stories Via Picture Card - Mulkan Andika Situmorang; Mimi Rosadi; Mastari Ramadhani; Ridho Kurniawan (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2024)
The purpose of this research is to describe the application of picture card media to the ability to write stories for elementary school students. This research was conducted in class V at the Bintaro Alam School. The strategies used are reading stories with pictures, arranging picture cards in sequence, and writing stories using picture cards. The results obtained through implementing this strategy are students' ability to write stories better. This can be proven that the ability to write stories using picture cards is said to be very good with a percentage of 90% of students able to write stories coherently. The presence of media helps students to write stories according to intrinsic elements.